2023
DOI: 10.3389/fpsyg.2023.1062829
|View full text |Cite
|
Sign up to set email alerts
|

Identities of the incumbent and the successor in the family business succession: Review and prospects

Abstract: IntroductionThe cognition and motivation of family business incumbents and the successors will directly influence succession behavior, yet they face identity challenges during succession due to the intersection of family and firm context, and their ability to overcome identity challenges will determine the success of the succession. However, as studies on their identity are fragmented and lack systematicity, there is a need to assess the relevant literature.MethodsDrawing from social identity theory (SIT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 144 publications
0
10
0
Order By: Relevance
“…These scholars show how the family's resources, norms, attitudes, and values influence the recognition of entrepreneurial opportunities that can potentially trigger changes in the family. Moreover, recent research highlights how the identity of the incumbent can better explain their emotions, cognition, and behavior to succession (Li et al, 2023;Radu-Lefebvre et al, 2021). In summary, retirement intentions precede succession planning, which means the incumbent leader of a family business will initiate and control the succession process.…”
Section: Theory Of Planned Behavior and Incumbents' Intended Age Of R...mentioning
confidence: 99%
See 1 more Smart Citation
“…These scholars show how the family's resources, norms, attitudes, and values influence the recognition of entrepreneurial opportunities that can potentially trigger changes in the family. Moreover, recent research highlights how the identity of the incumbent can better explain their emotions, cognition, and behavior to succession (Li et al, 2023;Radu-Lefebvre et al, 2021). In summary, retirement intentions precede succession planning, which means the incumbent leader of a family business will initiate and control the succession process.…”
Section: Theory Of Planned Behavior and Incumbents' Intended Age Of R...mentioning
confidence: 99%
“…In the case of family businesses, individual characteristics of the incumbent (such as age, gender, generation) and satisfaction with previous succession have been found to affect the propensity for succession planning and the willingness of the incumbent to step aside (Decker et al, 2016), as these factors influence an incumbent's goal adjustment capacity (Gagne et al, 2011). Incumbent's identity also plays a role in explaining emotions, cognition, and behavior during succession (Li et al, 2023;Radu-Lefebvre et al, 2021). This means that incumbent preparation for retirement impacts their expectations about succession.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…For instance, Saidat et al (2022) found family ownership had a negative impact on performance whereas, Guedes et al (2022) established that it had a positive impact in the long term. Family business performance is impacted by the work done by incumbents and successors (Li et al, 2023). In addition, Miroshnychenko et al (2023), points out that family involvement significantly impacts positively on the business' financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to systems theory, in a family business is a system of business and family overlaps, that links one another as a system (Poza, 2007). Through long-term investment and altruistic behaviour, a distinct, valuable, resource combination that blends family and commercial systems can be established and passed down for future generations (Li et al ., 2023). The socio-emotional wealth (SEW) perspective, which is based on stakeholder management theory has of late drawn interest in the field of family business (Acquaah, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation